Kunst im Park : Bundesgartenschau Berlin 1985. - Grzimek, Waldemar; Kosmologischer Park, Berlin; Franke, Senator Klaus; Halfmann, Jasper; Keller, Klaus; Schauer, Lucie (Berlin : Senator für Bau- und Wohnungswesen, 1985)
Biederbick, Christa ; Busching, Claudia ; Ciesluk, Karl ; Dunkel, Joachim ; Duschat, Klaus ; Erber, Wolfram ; Fehrenbach, Gerson ; Fischer, Lothar ; Fujiwara, Makoto ; Haisch, Eckhart ; Halfmann, Jasper ; Haug, Isolde ; Heinsdorff, Sebastian ; Herbrich, Peter ; Kluge, Silvia ; Köker, Azade ; Kremser, Engelbert ; Lieberknecht, Rolf ; Mahlmeister, Susanne ; Odious, Gruppe ; Oppenheim, Dennis ; Paolozzi, Eduardo ; Pfarr, Paul ; Press, Herbert ; Raeck, Karina ; Rheinsberg, Raffael ; Rieveschl, Gary ; Schmidt, Robert ; Schoenholtz, Michael ; Szymanski, Rolf ; Thürmer, Ludwig ; Vetter, Hans ; Voth, Hanns-Jörg ; Wargin, Ben ; Witting, Wigand ; Zillich, Clod ; Zilling, Jürgen
Kunst im Park : Bundesgartenschau Berlin 1985, Kosmologischer Park, Berlin, 1984
Duits
boek